The Pathology Laboratory Act 2007 explained. - Looi, Lai-Meng (2008)
The past century has seen tremendous changes in the scope and practice of pathology laboratories in tandem with the development of the medical services in Malaysia. Major progress was made in the areas of training and specialization of pathologists and laboratory technical staff. Today the pathology laboratory services have entered the International arena, and are propelled along the wave of globalization. Many new challenges have emerged as have new players in the field. Landmark developments over the past decade include the establishment of national quality assurance programmes, the mushrooming of private pathology laboratories, the establishment of a National Accreditation Standard for medical testing laboratories based on ISO 15189, and the passing of the Pathology Laboratory Act in Parliament in mid-2007. The Pathology Laboratory Act 2007 seeks to ensure that the pathology laboratory is accountable to the public, meets required standards of practice, participates in Quality Assurance programmes, is run by qualified staff, complies with safety requirements and is subject to continuous audit. The Act is applicable to all private laboratories (stand alone or hospital) and laboratories in statutory bodies (Universities, foundations). It is not applicable to public laboratories (established and operated by the government) and side-room laboratories established in clinics of registered medical or dental practitioners for their own patients (tests as in the First and Second Schedules respectively). Tests of the Third Schedule (home test blood glucose, urine glucose, urine pregnancy test) are also exempted. The Act has 13 Parts and provides for control of the pathology laboratory through approval (to establish and maintain) and licensing (to operate or provide). The approval or license may only be issued to a sole proprietor, partnership or body corporate, and then only if the entity includes a registered medical practitioner. Details of personnel qualifications and laboratory practices are left to be specified by the Director-General of Health, providing for a formal recognition process and room for revision as pathology practices evolve. Encompassed in the responsibilities of the licensee is the requirement that samples are received and results issued through, and management vested in, a registered medical or dental practitioner. This effectively prohibits "walk-ins" to the laboratory and indiscriminate public screening. The requirement for a person-in-charge in accordance with class and speciality of laboratory ensures that the laboratory is under the charge of the pathology profession. Examined carefully, the requirements of the Act are similar to laboratory accreditation, but are backed by legislation. Many of these details will be spelt out in the Regulations, and these in turn are likely to fall back on National professional guidelines, as accreditation does. Although not at first obvious, enforcement of the Act is based on self-regulation by pathology laboratory professionals. Sincere professional input is thus required to embrace its philosophy, ensure rational and transparent enforcement of legislation, and develop National guidelines for good pathology practices upon which enforcement may be based.